Purpose of Life of People with Mental Illness Living in the Community - Mizuno, Eriko; Sakai, Ikue (Journal of Japan Academy of Nursing Science, 2011)
Purpose: The purpose of this study was to describe the concrete contents and characteristics, experiences which affected the purpose of life of people with mental illness living in the community for three years or more. Method: Using a semi-structured interview, seventeen subjects participated in the study. Interviews were analyzed by qualitative description. Result: The data was classified into 5 categories related to purpose of life: personal relationships with others, positive feelings toward current life, hobbies, religion, and work. In addition, 6 categories of factors emerged which affected their purpose of life: self-realization of their symptoms and illness, positive recognition and advice by others, current life, intentional interpersonal relationships, relation with the family, and hard to notice one's purpose of life. Conclusion: Most of the purposes of life of people with mental illness were the existence of other people, positive feelings toward current life, and current interests. And, the purposes of life existed variously in usual life. It was thought that the relation of others was important to people with mental illness, because there is the person who is hard to notice one's purpose of life.